Виклики та загрози в глобальному кіберпросторі: заходи з підвищення кібербезпеки у сучасному світі - Атаманюк, Ростислав Романович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The text examines current cybersecurity issues in the modern world, focusing on the rise of cyber threats and identifying their general and specific aspects. Among the primary threats highlighted are cyber-attacks, cyber espionage, and cyber terrorism, which can lead to significant consequences for economic activities, infrastructure, and national security. It is noted that the increasing volume of personal information in the global cyberspace poses a threat of misuse. To effectively counter these threats, the author recommends a comprehensive approach to cybersecurity. This includes the necessity of a systematic and continuous approach to protection, regular updates of software and hardware, the use of strong passwords and two-factor authentication, conducting regular security audits, and protection against phishing and internal threats. Emphasis is also placed on the importance of collaboration, information exchange, and education as effective means to combat cyber threats. Overall, the text underscores that ensuring cybersecurity requires not only technical measures but also cultural changes, collaboration, and education to guarantee reliable protection in a world where cyber threats continually grow in complexity and scale.